Cripping the Story of Overcoming: An Analysis of the Discourses and Practices of Self-Regulation in Early Childhood Education and Care (ECEC) - Maria Karmiris; Adam Davies (Studies in Social Justice, 2024)
This paper applies crip theory (McRuer, 2006, 2018) as well as other key conceptual tools from disabled childhood studies (Runswick-Cole et al., 2018) and disability studies in education (Cousik & Maconochie, 2017) as a tactic intended to question and resist the story of overcoming as it manifests itself within the discourses and practices of self-regulation in early learning classrooms. This paper offers a brief overview of the range of self-regulation strategies enacted within educational settings in Ontario, Canada, that purport to support young children in overcoming themselves on their way to normalcy. This paper also engages in crip theory as a strategy to both question and disrupt the taken for granted assumption that self-regulation entails a return towards or a sustaining of the efficient and productive neoliberal individual in school systems. Finally, this paper considers how we might not only invite but embrace the disruptions that occur when embodied differences refuse to be overcome by demands to self-regulate. Ultimately, a key aim of this paper is to resist how discourses and practices of self-regulation in Early Childhood Education and Care (ECEC) establish the overcoming narrative as a means to cure, fix or exclude embodied differences while contemplating the vibrant possibilities embedded within learning with and from disabled childhoods.